Nutrient Accumulation During Vegetative and Reproductive Growth Affected by Endogenous and Exogenous Phosphorus Applications in Maize Crop. Issue 7 (12th April 2023) - Saeed, Muhammad Tariq; Wahid, Muhammad Ashfaq; Riaz, Umair; Nadeem, Muhammad; Farrukh Saleem, Muhammad; Aziz, Tariq; Kausar, Salma; Cheema, Mumtaz
ABSTRACT: Although maize ( Zea mays L.) crop has high production potential for forage and grain, however it requires efficient managerial practices for optimum yield. Adequate nutrients for optimum growth led to good vegetative and reproductive growth. Field studies were conducted to evaluate the effects of two endogenous seed phosphorus (P); i.e. SLP: seed with low endogenous phosphorus (1.5 mg kg −1 seed dry weight), and SHP: seed with high endogenous phosphorus (3.2 mg kg −1 seed dry weight). Pre-categorized seeds were tested against five rates of exogenous soil P, namely, (1) control: no P (0 kg P ha −1 ); (2) 50 kg P ha −1 ; (3) 100 kg P ha −1 ; (4) 150 kg P ha −1 ; and (5) 200 kg P ha −1 . Seeds having different P contents depicted non-prominent effects on accumulation patterns with few exceptions of P (at physiological maturity (R6) and of potassium (K) (at grain filling (R4) and R6); exogenous P expressed significant effects. Nitrogen (N), P, K, zinc (Zn), and boron (B) exhibited differential accumulation behavior during maize growth. Nitrogen expressed accumulation from tasseling (VT) to R4; however, P, K, Zn, and B depicted remobilization from VT to R6. Maximum accumulation efficiency of P (50.7%), Zn (46.9%), and B (51.4%) was observed from VT to R4 growth, whereas maximum response of K (60.3%) and N (21.8%) was witnessed from R4 to R6, representing variant source-sink capacities. Boron depicted greater remobilization under low exogenous P applications. Results suggest that exogenous P application severely affects nutrient accumulation during pre- and post-grain filling growth.